2012
DOI: 10.1590/s1980-57642012dn06040013
|View full text |Cite
|
Sign up to set email alerts
|

Participation in nighttime activities in the genesis of depression in public school teachers from the State of Pernambuco, Brazil

Abstract: Teachers often undertake nighttime work involving exam corrections, projects and devising lesson plans in their homes. Many present excessive daytime sleepiness (EDS) and depression.ObjectiveThe objective of this study was to evaluate EDS and depression in teachers from public schools.Methods201 female teachers were evaluated in the district of Quipapá/PE, Brazil. Among the study sample, 38 working 1 shift (CONTROL 1), 40 working 2 shifts (CONTROL 2) and 123 working 3 shifts (WTeachers-3T). The subjects were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
5
0
2
Order By: Relevance
“…Occupational stressors such as work overload and low salary are correlated with high stress and low job satisfaction; low job satisfaction was identified as a predictor of major depressive disorder among the teacher population [2,4]. A study of elementary teachers in Brazil found that teachers who worked more had poorer mental health including depression, anxiety and sleep disorders [3]. Work environment and conditions not only impact the psychological wellbeing of teachers but also influence their ability to adequately perform job duties.…”
Section: Mental Health Of Teachersmentioning
confidence: 99%
See 2 more Smart Citations
“…Occupational stressors such as work overload and low salary are correlated with high stress and low job satisfaction; low job satisfaction was identified as a predictor of major depressive disorder among the teacher population [2,4]. A study of elementary teachers in Brazil found that teachers who worked more had poorer mental health including depression, anxiety and sleep disorders [3]. Work environment and conditions not only impact the psychological wellbeing of teachers but also influence their ability to adequately perform job duties.…”
Section: Mental Health Of Teachersmentioning
confidence: 99%
“…Work environment and conditions not only impact the psychological wellbeing of teachers but also influence their ability to adequately perform job duties. Poor sleep and sleep disorders were associated with depression and impaired cognition which impacted attention, concentration and memory and led to low personal and work performances [3,5,12].…”
Section: Mental Health Of Teachersmentioning
confidence: 99%
See 1 more Smart Citation
“…Teachers worldwide demonstrate susceptibility to mental health issues such as depression, anxiety and stress based on the multitude of primary stressors they encounter, including a lack of resources, a pressure to fulfill multiple roles, interpersonal troubles, demanding working conditions, low student achievement and excessive workload [1][2][3][4][5]. Further, numerous studies have demonstrated that these primary stressors threaten the psychological wellbeing of teachers internationally [6][7][8][9][10]. Poor psychological wellbeing may contribute to problems such as low teacher performance and teacher burnout, which in turn may lead to Resiliency and mental health of teachers costly social and economic consequences, such as poor academic outcomes for students and low retention rates of quality teachers [8,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Diversos estudos, têm evidenciado a depressão como uma das doenças ocupacionais que mais causa o afastamento do trabalho, o absenteísmo, o presenteísmo e a rotatividade entre os professores (Gomes & Quintão, 2011;Almeida, Pereira, & Duarte, 2012;Correia et al, 2012;Batista, Carlotto & Moreira, 2013;Sacandolara, Wietzikoski, Gerbasi, & Sato, 2015;Silva & Carvalho, 2016). Esta, entre outras formas de adoecimento mental, tem levado a profissão docente a ser considerada de alto risco pelos órgãos internacionais (Organização Internacional do Trabalho [OIT], 2017).…”
Section: Introductionunclassified